Biventricular Morphology and Function Reference Values Derived From a Large Sample of Healthy Chinese Adults by Magnetic Resonance Imaging - Zhang, Zhen; Ma, Qiaozhi; Gao, Yiyuan; Cao, Lizhen; Zhu, Chengcheng; Zhao, Zhiwei; Zhao, Jun; Zeng, Linan; Lou, Mingwu; Pohost, Gerald M.; Li, Kuncheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Quantification of cardiac structure and function is essential for diagnostic interpretation and clinical decision making. We sought to establish cardiovascular magnetic resonance (CMR) reference values of left and right ventricular (LV and RV) morphology and function based on a large sample of healthy Chinese adults. Methods: Five hundred fifty validated healthy Chinese adults (aged 21–70 years; 323 men) free of hypertension, diabetes, and obesity were included in this study. All the subjects were stratified by gender (men and women) and age decades. On cine CMR, measurements of biventricular end-diastolic, end-systolic, and stroke volumes (EDV, ESV, and SV), ejection fraction (EF), and end-diastolic LV wall thickness (LVWT) and mass (LVM) were obtained. Results: Men had greater LVEDV (111.6 ± 19.8 vs. 94.6 ± 15.6 ml), LVESV (36.5 ± 9.8 vs. 28.2 ± 7.9 ml), LVM (121.1 ± 19.9 vs. 86.1 ± 14.5 g), global end-diastolic LVWT (8.1 ± 1.1 vs. 6.7 ± 1.0 mm), RVEDV (128.0 ± 23.6 vs. 101.7 ± 17.0 ml), and RVESV (53.5 ± 13.7 vs. 36.8 ± 8.9 ml), while women had greater LVEF (67.5 ± 5.4 vs. 70.4 ± 5.7%) and RVEF (58.5 ± 5.2 vs. 64.0 ± 5.3%) (all p < 0.001). For both men and women, age was negatively correlated with LVEDV (r = −0.31 and r = −0.32), LVESV (r = −0.37 and r = −0.47), RVEDV (r = −0.31 and r = −0.29), and RVESV (r = −0.33 and r = −0.44), while it was positively correlated with LVEF (r = 0.28 and r = 0.43) and RVEF (r = 0.28 and r = 0.41) (all p < 0.001). Aging was associated with increasing global end-diastolic LVWT and LVM/LVEDV in both sexes (all p < 0.001). Older age was associated with increasing LVM only in women (r = 0.36, p < 0.001), not in men (r = 0.05, p = 0.359). Conclusions: We systematically provide age-, sex-, and body size-specific CMR reference values for biventricular morphology and function based on a large sample of healthy Chinese adults. Biventricular structure and function are significantly associated with age and sex.